Orchitis Sebagai Komplikasi Infeksi Mumps (Gondongan): A Case Series - Rizqiani Astrid Nasution; Oktadoni Saputra (Medula, 2026)
Mumps is a viral infectious disease that is generally self-limiting but may lead to serious complications, including orchitis, which can adversely affect future fertility, particularly in adolescent males. This case series aims to describe the clinical manifestations, diagnostic approach, and management of mumps-associated orchitis in a prepubertal child and an adolescent. Two male patients aged 11 and 15 years who were treated at Dr. H. Abdul Moeloek Hospital in 2024 were diagnosed with mumps orchitis. Both patients initially presented with parotid gland swelling followed by fever, scrotal swelling, and testicular pain several days later. Diagnosis was established through history taking, physical examination, laboratory investigations, and scrotal ultrasonography in one patient. Ultrasonographic findings demonstrated epididymo-orchitis characterized by enlargement of the testis and epididymis with increased vascularity. Both patients received supportive management, including hydration and analgesics, with additional therapies administered according to clinical indications. Clinical improvement was observed in both patients during hospitalization. This report highlights that orchitis may occur as a complication of mumps in both prepubertal and adolescent males, including those with a complete immunization history. Early recognition of orchitis symptoms in patients with mumps is essential to ensure timely diagnosis and appropriate management, thereby reducing the risk of long-term reproductive complications.